Suara Genta dalam Ajaran Kediatmikan - Ni Kade Seri Andayani (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
The beauty of kasanah and the ritual implementation of yajna balinese Hindu community is seen from various activities carried out as well as supporting facilities of yajna activities. The performance of yajna is actually a theatrical performance that is undiscised when reviewed from an art point of view. Later in its implementation there are five tones as a complement to the activity and one of them is the voice of Genta also called Nada Brahman. Genta is a tool used by stakeholders / pinandita to accompany the spell chanted. In addition to being a means of puja genta from ampek sound that gives rise to cosmic vibrations can also support kundalini fire in humans. Through a qualitative approach and various text studies, further assessment of this needs to be done. It can be explained that Genta corresponds to the concept of the pengiders to the east, with the aksarasuci being 'Sa', the god is Iswara, the war is white and inside man is housed in the Heart. In addition to the concept of sound and tone in the use of genta as its facilities, from the aspect of voice dialogue genta also plays a role in improving the science of dialogue. This is supported by various lontang that explain that the genta that emits the loud sound is the generator of cosmic vibrations and can evoke 7 (seven) chakras that exist in humans. The rise of these 7 chakras will raise the fire of kundalini which affects the disusedness that a person has. Genta in this case became known as Genta pinaruh pitu, a aguron-gorun concept that gave teachings to the people, especially Hindus in Bali about ancient teachings as one of the ways to achieve release.